Regional Cohesion in Europe 2020-2021 Insights from the EIB Investment Survey - European Investment Bank (European Investment Bank, 2021)
EU Cohesion Policy aims to strengthen economic, social and territorial cohesion across the European Union and to correct imbalances between countries and regions. The green and digital transition are key priorities of Cohesion Policy for the next years. Cohesion support 2021-2027 is focused on five key policy objectives to support growth: A more competitive and smarter Europe A greener, low-carbon transition towards a net zero carbon economy A more connected Europe by enhancing mobility A more social and inclusive Europe A Europe closer to citizens by fostering the sustainable and integrated development of all types of territories. EU funds will support investment across these policy objectives with a particular focus on a smart and green Europe. However, the COVID-19 pandemic risks deepening divergences between citizens, territories and firms. Firms across the EU will need to adapt to the post-pandemic environment and megatrends, notably digitalization and climate change, to stay competitive looking ahead. The EU has committed to a joint recovery centered on fostering the transition towards a greener and smarter economy across the EU. The extent to which this will mitigate the risks of rising inequalities and divergences across firms depends not least on support for cohesion. Data coming from the EIB Investment Survey (EIBIS) provides a unique tool to gain insights on how non-financial corporates in cohesion and non-cohesion regions are behaving. EIBIS information sheds new light on investment needs and gaps, financing requirements as well as firm activity on innovation, digitalization and climate change.